Pemetaan Pemangku Kepentingan Dalam Program Kampung Iklim Di DKI Jakarta - Dewi Nurhasanah; Yogi Gumilar Saeful Akbar (Universitas Medan Area, 2022)
This article aims to map stakeholders and their roles in the implementation of the Climate Village Program (Proklim). This research focused on two study locations, namely RW 06 Kelurahan Kebon Blank (Central Jakarta) and RW 07 Kelurahan Kebayoran Lama Selatan (South Jakarta). The selection of these two study locations was based on high initiative and sustainability in the implementation of Proklim to address problems related to climate change. The data in the study were collected through interviews, field observations, and document analysis which were then analyzed qualitatively. The analytical method used is a two-dimensional matrix mapping that describes the strengths and interests (two-dimensional power-interest matrix) of each stakeholder and the division of their roles. From the results of research in the field, it was concluded that the key actors in the implementation of Proklim were dominated by local people living in the area, because local residents were the parties who directly felt the benefits of Proklim and were parties who had direct access to resources and had a high interest in the implementation. Proclam at the site level.